Asas Itikad Baik dalam Perjanjian Jual Beli Barang Melalui Media Elektronik (E-Commerce) - I Wayan Agus Grahadi Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2020)
Abstract—Technological developments affect all aspects of life that make life easier or more instant. One aspect of this technology is affected by the purchase agreement. This agreement was initially carried out by businessmen meeting with a buyer in a place (the market), today this agreement can be done simply by using mobile phones that have internet we are able to make buying and selling the so-called E-Commerce. As for the formulation of the problem 1. How is the validity of the Sale and Purchase Agreement using Electronic Media (E-Commerce) for the parties who make it? How is the Good Faith Principle in the Sale and Purchase Agreement of Goods using Electronic Media (E-Commerce)? This research uses normative research methods. The results of this study are Effect of E-Commerce has changed the way a person to transact in the electronic media have a positive impact for both side. When there is a positive impact then of course there are negative impacts, the negative impact entrepreneurs often commit fraud in transactions because they do not meet in person only meet in cyberspace alone. So in the world of E-Commerce importance of implementing in good faith greatly influence the nets of a business because when it has been using the good faith of both parties will not commit fraud with each other.